Urban-rural difference in community willingness to isolate during COVID-19 pandemic in Benue State Nigeria 2021 - Okon, Ubong Akpan; Olayinka, Adebola; Mwansa, Pamela; Mwansa, Hope; Usman, Rabi (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 2019 is a highly infectious viral disease reported across more than 210 countries of the world. Isolation is a very critical component of COVID-19 public health responses were infected or exposed persons are separated from the unexposed individual for the purposing of protecting and preventing or containing disease spread. Our study assessed and compared community willingness to isolate during COVID-19 pandemic among urban and rural dwellers. Methods: A multi-stage comparative cross-sectional study was used to assess respondents’ willingness to isolate between January and April 2021. Response was scored and each composite scores were converted to a percentage. The assessment was done using three questions with a maximum score of 15. A score of ≥80% of the maximum score was categorized as more willing to quarantine or isolate, score from 51% to 79% was categorized as slightly willing to quarantine or isolate while ≤50% was categorized as less willing to quarantine or isolate. Data was analysed using STATA SE 64 software and level of significance set at 5%. Categorical variables were summarised as frequency and percentages and presented in tables urban and rural comparisons were done with Chi square test and the corresponding p-values presented. Results: One thousand three hundred and thirty-one respondents recruited into the study had a mean age of 33.7±12.83. Urban respondents aged 25-34 years were 36.64% (358) while rural respondents 31.94% (145) were aged 25-34 years (p=0.013). Most the respondents in both urban and rural communities were females 58.15% (574) and 55.73% (253) respectively. 549 (56.19%) of urban respondents were willing to be quarantined after contact with a suspected COVID-19 patient when compared with the rural respondent 292 (64.32%). Only 524 (53.63%) of urban respondents were willing to isolate after having had contact with a confirmed patient compared with the rural respondents 277 (61.01%). More than half of the respondents in urban and rural 629 (64.38%) and 303 (66.74%) respectively showed their willingness to isolate if confirmed to have COVID-19. Overall, 758 (77.58%) of the respondents were willing to go into isolation during COVID-19 pandemic when compared with rural communities 377 (83.04%) of respondents (p value =0.06). Conclusions: Willingness to isolate during COVID-19 pandemic is higher among rural dwellers than the urban dwellers.